The measurement of service quality in New Zealand heritage attractions : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Quality Management at Massey University, Department of Production Technology - Tan, Sin Week (Massey University, 1998)
Museums and historic places are part of our national heritage, they have been consistently rated as the most popular destinations for overseas tourists to New Zealand. To attract tourists, the industry needs to understand what the tourists' needs are, what attracts them and how satisfied they are with their experience. An initial investigation into the quality management practice in the New Zealand tourist industry was carried out using a mail survey in April, 1995. It aimed at providing a better understanding of the current status of quality management practice and identify the needs of quality management of the New Zealand tourist industry. The findings of the survey identified a lack of awareness of Total Quality Management and quality management in the New Zealand tourist industry. This indicates that there could be potential for the tourist industry operators to improve their performance and competitiveness through the introduction of TQM and there is a need for a quantitative tool for measuring service quality in the tourist industry. A modified SERVQUAL tool was developed to assist heritage attraction operators to measure their service quality. The tool was tested, using visitor surveys at three heritage attractions. This research shifted the focus of performance assessment from the institution to the customer and measured the customer satisfaction instead of just the number of visitors. In the New Zealand heritage attractions, four service quality dimensions were identified: tangible, peripheral service, staff related functions and access. The importance of service quality dimensions is different from other service sectors and service quality dimensions are not generic across the service industries. The different statistical analysis techniques used in this research include factor analysis, correlation analysis, ANOVA and correspondence analysis. Valuable information was obtained from these analyses which could be used by management in assessing their performance from the customer's perspective, developing strategic plans to improve service delivery and to improve their business competitiveness.
Irregular pagination: missing pages 263-266, however no content appears to be missing
Keywords: Tourism; Quality control; Heritage sites; Customer service; New Zealand